2022
DOI: 10.1002/bit.28269
|View full text |Cite
|
Sign up to set email alerts
|

Poly (beta‐amino ester) as an in vivo nanocarrier for therapeutic nucleic acids

Abstract: Therapeutic nucleic acids are an emerging class of therapy for treating various diseases through immunomodulation, protein replacement, gene editing, and genetic engineering. However, they need a vector to effectively and safely reach the target cells. Most gene and cell therapies rely on ex vivo gene delivery, which is laborious, time‐consuming, and costly; therefore, devising a systematic vector for effective and safe in vivo delivery of therapeutic nucleic acids is required to target the cells of interest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 191 publications
0
8
0
Order By: Relevance
“…134,142 New strategies continue to be developed to overcome these challenges and enhance PBAE-based therapeutic delivery. 143 To summarize, polymers are frequently used as mRNA delivery vehicles because they are structurally diverse and relatively easy to synthesize. Additionally, they can undergo various modifications, so their chemical and physical properties can be optimized for specific therapeutic applications.…”
Section: Non-viral Delivery Carriers For Mrnamentioning
confidence: 99%
See 1 more Smart Citation
“…134,142 New strategies continue to be developed to overcome these challenges and enhance PBAE-based therapeutic delivery. 143 To summarize, polymers are frequently used as mRNA delivery vehicles because they are structurally diverse and relatively easy to synthesize. Additionally, they can undergo various modifications, so their chemical and physical properties can be optimized for specific therapeutic applications.…”
Section: Non-viral Delivery Carriers For Mrnamentioning
confidence: 99%
“…PBAEs can also be chemically modified with ligands, peptides, and PEG to further reduce toxicity and improve selective delivery to specific organs. To achieve controlled gene delivery, Lee and co-workers designed PBAEs that can be used for on-demand release of nucleic acids in response to UV light and pH triggers . However, PBAEs show some weaknesses as they can be unstable in physiological fluids and in long-term storage. , PBAEs also have relatively low binding efficiency to nucleic acids and can release nucleic acid cargo off-target. , New strategies continue to be developed to overcome these challenges and enhance PBAE-based therapeutic delivery …”
Section: Non-viral Delivery Carriers For Mrnamentioning
confidence: 99%
“…Furthermore, transfection efficiency of PBAEs can be greatly influenced by the buffering system, imposing significant constraints on its widespread application. For instance, it was reported that in contrast to monovalent buffering systems, such as sodium acetate (NaAc), divalent buffering systems such as magnesium acetate and calcium acetate enhanced the transfection efficiency of PBAE‐based vectors 165 …”
Section: Gf Gene Deliverymentioning
confidence: 99%
“…PBAE exhibits a highly adaptable chemical structure and is readily biodegradable. It can be synthesized by the Michael addition reaction [ 180 ]. The first attempt to use PBAE as a nucleic acid delivery vector was reported by Langer's team.…”
Section: Nanomaterials For Nucleic Acid Deliverymentioning
confidence: 99%